2015
DOI: 10.1001/jamasurg.2015.1698
|View full text |Cite
|
Sign up to set email alerts
|

Reading Habits of General Surgery Residents and Association With American Board of Surgery In-Training Examination Performance

Abstract: Most residents reported reading consistently for patient care throughout the year. Daily studying and textbook use were associated with higher ABSITE scores on univariate analysis. Scores on the USMLE 2 and MCAT, as well as resident attitude regarding the importance of the ABSITE results, were independent predictors of ABSITE performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 15 publications
(38 reference statements)
0
18
0
Order By: Relevance
“…Possible changes can include allocating more time for resident self-study, offering review sessions which are tailored to meet the needs of residents and providing effective access to learning content. Residents may also consider maintaining a regular study schedule throughout the year, which has been shown to result in improved medical knowledge and better performance on standardized examinations [14, 15]. Although we did not assess the effectiveness of electronic or E-learning in our study, residency programs could also consider complementing traditional didactic methods with E-learning.…”
Section: Discussionmentioning
confidence: 99%
“…Possible changes can include allocating more time for resident self-study, offering review sessions which are tailored to meet the needs of residents and providing effective access to learning content. Residents may also consider maintaining a regular study schedule throughout the year, which has been shown to result in improved medical knowledge and better performance on standardized examinations [14, 15]. Although we did not assess the effectiveness of electronic or E-learning in our study, residency programs could also consider complementing traditional didactic methods with E-learning.…”
Section: Discussionmentioning
confidence: 99%
“…While didactic lectures are a mainstay of medical education, it has been observed that medical residents fail to show learning benefit from lecture series in terms of effect on standardized examination scores 9 or long-term practice behaviours. [16][17][18] Our results reflect that junior residents find these sessions to be valuable.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, structured reading habits 7,8 and the use of specific study materials 7,9 were found to be positive predictors of successful performance. Studies have established that resident performance on these in-training examinations goes on to correlate with subsequent performance on licensing examinations.…”
Section: Introductionmentioning
confidence: 94%
“…Other avenues of evaluation include the Fundamentals of Laparoscopic Surgery tasks for surgical skills acquisition, online surgical courses with embedded assessments, 3 standardized patient encounters for interpersonal and communication skills, and mock oral examinations for patient care-related decision-making. 44 Innovations in models and simulation technology for surgical training and objective evaluation by the Association for Surgical Education are eagerly anticipated. 45 Regular evaluation of surgical residency models should be done to ensure that programs are meeting their training goals in the areas of rotations, student quality of life, operative experience, ABSITE, faculty, and hospital patient care metrics.…”
Section: Active Learning In the Context Of Surgical Educationmentioning
confidence: 99%